2001
DOI: 10.1161/hq1001.096651
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Evaluation of the Effects of Diet and Lipid-Lowering Therapy on Atherosclerotic Plaque Development in Mice

Abstract: Abstract-Quantitative characterization of atherosclerotic plaque composition with standard histopathological methods remains limited to sectioned plaques. Raman spectroscopy enables nondestructive quantification of atherosclerotic plaque composition. We used Raman spectroscopy to study the effects of diet and lipid-lowering therapy on plaque development in apolipoprotein (APO) E*3-Leiden transgenic mice. Raman spectra were obtained over the full width and entire length of the ascending aorta and aortic arch. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…31,32 The plaque composition changes seen following statin therapy have been studied by Raman microscopy, showing a decrease in atherosclerotic plaque size. 33 These studies, however, have not demonstrated how statins directly alter lipid crystals, thereby stabilizing adverse components of stable plaques. We demonstrated that the chemical profiles of lipid crystals were changed by statin therapy using multiplex CARS.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The plaque composition changes seen following statin therapy have been studied by Raman microscopy, showing a decrease in atherosclerotic plaque size. 33 These studies, however, have not demonstrated how statins directly alter lipid crystals, thereby stabilizing adverse components of stable plaques. We demonstrated that the chemical profiles of lipid crystals were changed by statin therapy using multiplex CARS.…”
Section: Discussionmentioning
confidence: 99%
“…It can potentially quantify cholesterol in plaque and can monitor the effects of atheroma-modifying therapy. 23,31 Raman spectroscopy is limited by the fact that blood absorbs laser light and that it is 1-dimensional. 23 It can, however, be combined with other imaging techniques to provide important information about plaque composition.…”
Section: Emerging Diagnostic Techniques: Noninvasive Techniquesmentioning
confidence: 99%
“…[46] Whilst this remains a proof-of-principal study there is potential for extension to studies in man and although not demonstrated remote sensing could be achieved by coupling via a fibre optic probe. [46] Similarly, Raman spectroscopy has been implemented to monitor organ rejection in patients following transplant procedures. [48,49] While not directly involving the detection of disease, it is possible that the processes which led to transplant were the result of disease, for example, coronary heart or chronic kidney disease.…”
Section: Raman Spectroscopy and Ex Vivo/in Vivo Applications For The mentioning
confidence: 99%
“…[45] Raman spectroscopy is not limited to the detection of cancer and research has postulated that the method could be used for the characterisation and monitoring of atherosclerotic plaques. [46] In the UK alone coronary heart disease and the conditions which stem from it cost an estimated £19 billion.…”
Section: Raman Spectroscopy and Ex Vivo/in Vivo Applications For The mentioning
confidence: 99%
See 1 more Smart Citation